Pelatihan Kepemimpinan Dan Pembinaan Untuk Meningkatkan Kemampuan Para Pengurus OSIS SMA Dan SMK Negeri Di Jakarta Utara - Muhammad Ramaditya; Syahrul Effendi; Faris Faruqi (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2020)
In the modern era, the leadership values and processes that must be passed by someone to become a leader has been changed. The evolution of mind and social life has changed the paradigm of modern humans in the view of the concept of leadership. To be a leader, a person must speak and train himself to have the character, abilities or qualities that should be owned by leaders. The Students who manage intra-school organizations (OSIS) are one of the forerunners of future leaders in the future and have an interest in driving change in their respective schools so that they become better. As a form of caring in building a leadership model that has integrity, Indonesia College of Economics conducts leadership training and coaching for OSIS administrators in SMA & SMK Negeri as well as the private sector in North Jakarta. The method used in this training consisted of lecture activities, question and answer sessions, discussion of case studies, by explaining the basic concepts of visionary leadership, participative leadership styles, change leadership and how to make decisions correctly. After this training, it is hoped that the student council officials will possess and demonstrate leadership motivation skills that are ready to challenge and can inspire students in their respective school environments.